Chiral edge states for phononic crystals based on shunted piezoelectric materials. (January 2022) - Tian, Yuping; Zhang, Wei; Tan, Zhuhua; Cho, Chongdu
Abstract: Chiral materials provide a new platform for achieving wave manipulation. The robust edge states of chiral materials can propagate at interfaces that are immune to a variety of defects that have been demonstrated in acoustic and photonic systems, but rarely explored in bulk elastic systems. Here, we construct a chiral phononic crystal using piezoelectric media with shunted inductances and also establish an effective Hamiltonian model. Polarizations of the eigenmode fields from the lowest band to the highest band can be transmitted by modulating the increase of the shunted inductances in a clockwise or counterclockwise direction, which results in a chiral structure and induces an edge state. The robust and strong wave propagation of edge states has been demonstrated numerically. Based on the robust nature of the edge state of the current chiral structure, strong energy harvesting efficiencies can be achieved directly at arbitrary piezoelectric positions of the edges in chiral phononic crystals, indicating that they are also robust to positional defects and inductance perturbations. Our chiral piezoelectric phononic crystals have the potential to control elastic waves and realize robust energy harvesting.